Perlindungan Hukum Konsumen Bagi Penerima Vaksin Covid-19 - Vera Waty Simanjuntak; La Ode Angga; Lucia Charlota Octovina Tahamata (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2021)
Introductioan: The government continues to carry out Covid-19 vaccinations in Indonesia to protect and strengthen the health system as a whole, as well as maintain productivity and reduce the social and economic impact of the community.Purposes of the Research:  Purpose of Writing/Research: knowing and analyzing the covid 19 vaccine and its impact on the human body as well as knowing and analyzing legal legal protection for recipients of the covid-19 vaccine. Methods of the Research:  The method used in writing this paper is literature study and observation. The main types of references used in the study of literature are books, journals and scientific articles. The data is used as a basis for analyzing and explaining the problem in a discussion. The analysis technique is descriptive argumentative. Meanwhile, observations and interviews were conducted with civil law lawyers at Pattimura University. Results of the Research: The results of the study show that the government has a responsibility to guarantee the rights of citizens to health, so that when these obligations are violated and cause harm, the government has committed acts against the law, community with an organized approach to achieve maximum results. In the implementation of vaccination, the government must provide clear information to the public so that people are not afraid to participate in vaccination. The government must also provide clear information to the public that after being vaccinated, the community must continue to apply health protocols for mutual safety.